Single CCCTA-based sinusoidal oscillator with voltage and current outputs - Channumsin, Orapin; Tangsrirat, Worapong (My University, 2014)
The sinusoidal oscillator which produces both voltage and current outputs simultaneously is described in this study. The described oscillator circuit contains only one current-controlled conveyor transconductance amplifier (CCCTA) and three grounded passive components. The circuit provides advantage features, such as, use of all grounded passive components, electronic tuning of oscillation condition and frequency and low sensitivity figures. Circuit performance verification is verified by PSPICE program with attractive results.
Keywords: Current-controlled conveyor transconductance amplifier (CCCTA); Current-mode circuits; Sinusoidal oscillator; Voltage-mode circuits